Self-inspection in educational institutions. Requirements and methodological procedures - Diardes Sanjurjo, Isabel; Herrera Martínez , Lázara; Martínez-Ochoa , Héctor Diego; Guerra Roman , Juana Yamila; Bastida Lugones , Lázara (Revista Minerva, 2023)
This investigation is part of the studies related to the improvement of the National System of Education. It is unquestionable that the improvement of the quality is indissolubly associated to the evaluation of the educational process whose objective is to provide tools on the operation of the activity of school internal inspection and the results that they are obtained in the different levels. so much for those that have responsibility in their address and administration, like it stops each one of the factors that you/they participate in him. As problematic they are limitations in the internal forces of the institutions, there are lacks in the most efficient answers to the requirements of the educational community, there are lacks in achieving a system that allows to obtain a valid and systemic information to measure and to evaluate the behavior and the efficiency in the different stadiums of the process and to identify the factors that explain in more proportion the achievements and inadequacies of the educational institution, keeping in mind the acting of each one of those implied in the development and results of the process, sustained in a conception and dialectical-materialistic and humanist method, when applying survey, revision of documents and observation to classes that it puts in the center from their attention to the human resource. As a result a body of demands is presented and to proceed methodological of the activity of school internal inspection in the educational institution. The activity of Inspection contributes to the achievement of the quality of the education and in consequence the process that is carried out inside each institution, the internal inspection.
Keywords: inspection; internal; improvement; quality; participation